A Novel GTS Mechanism for Reliable Multihop Transmission in the IEEE 802.15.4 Network. (29th January 2012) - Choi, WoongChul; Lee, SeokMin
Abstract : The IEEE 802.15.4 standard provides Guaranteed Time Slot (GTS) mechanism for reliable transmission. GTS mechanism is suitable for transmitting time-sensitive data because it allocates time slots to a specific node. However, the GTS mechanism in the standard can be used only for one-hop communication. This paper proposes and implements a multihop GTS mechanism for reliable transmission in multihop networks. Simulation results using NS-2 show that low delay and high delivery ratio can be achieved using the proposed mechanism.